Education politics and contingency: Belief, status and trust behind the Finnish PISA miracle - Hannu Simola; Risto Rinne (Recherches en Éducation)
Many rather non-historical and decontextualised concepts such as efficiency, accountability and quality are colonising the educational world undisputed and uncontested, largely due to the fact that they have been internationally advocated. Comparative education is still suffering from certain methodological deficits and serious under-theorisation. In this article we are trying to shed more light to the comparative resarch by presenting the promising concepts of continguency, coincidence and Spielraum to be taken seriously. We are also presenting the case of Finnish success of PISA by applicating those concepts. What we are trying to illustrate are three rather common beliefs emanating from the recent national discussion in Finland. All of these beliefs seem to be rather distinctive compared to other nations’ beliefs and discussions, and they certainly have at least some generative roots in Finnish national history. The first is that the Finns share a strong belief in schooling, the second that teaching is rather highly appreciated as a profession in Finland, and the third that the Finnish comprehensive school enjoys rather high trust on the part of parents, authorities and politicians. All three are national ‘truths’ in a way widely accepted even though there is not too much empirical research evidence behind them. They are definitely constituent parts of the national self-understanding in terms of education. In this article we address the question of why these beliefs exist rather than whether they are true or not. Finally, we also impugn traditional functionalist and rationalist explanations of comparative research in education.